Variables of the family, school, and social environment context that determine bullying in adolescents in Medellín, Colombia, 2014 (2017)
This study determines the prevalence of bullying and the variables that explain the phenomenon iin adolescents from educational institutions in Medellín. A survey involving school climate family functionality and bullying was applied in a representative